Biomarker predictors of cardiac hospitalization in chronic heart failure: a recurrent event analysis - Vorovich, Esther (2014)
BACKGROUND: Identification of heart failure (HF) patients at risk for hospitalization may improve care and reduce costs. We evaluated nine biomarkers as predictors of cardiac hospitalization in chronic HF. METHODS AND RESULTS: In a multicenter cohort of 1512 chronic HF outpatients, we assessed the association between 9 biomarkers and cardiac hospitalization using a recurrent events approach. Over a median follow-up of 4 years, 843 participants experienced one or more hospitalizations (total 2178 hospitalizations). BNP and TnI exhibited the strongest associations with risk of hospitalization [HR 3.8 (95% CI 2.9-4.9) and HR 3.3 (95% CI 2.8-3.9); third vs. first tertile]. sFlt-1 exhibited the next strongest association [HR 2.8 (95% CI 2.4-3.4)], followed by ST2 [HR 2.3 (95% CI 2.0-2.8)] and creatinine [HR 1.9 (1.6-2.4)]. Within ischemic/nonischemic subgroups, BNP and TnI remained most strongly associated. Except for creatinine, hazard ratios for all biomarkers studied were smaller within the ischemic subgroup, suggesting greater importance of cardio-renal interactions in decompensation of ischemic HF. CONCLUSION: While BNP and TnI exhibited the strongest associations with hospitalization, etiology-dependent associations for the remaining biomarkers suggest etiology-specific mechanisms for HF exacerbation. sFlt-1 exhibited a strong association with cardiac hospitalization, highlighting its potential role as a biomarker of HF morbidity.